Peran Hukum Dalam Menjamin Transparansi dan Akuntabilitas Tata Kelola Perusahaan - Putri, Devindya Citra Prameisti; Damayanti, Winda Agustina; Lutfianti, Alya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Law plays a role as the main regulator in implementing the principles of transparency and accountability. Transparency involves the disclosure of clear, accurate and timely information, including announcements of PT establishments, openness in ownership information, and openness in open management. Accountability refers to individual or organizational responsibility for company actions and decisions, as well as the obligation to report, explain and account for company performance results to stakeholders. The role of law in ensuring transparency and accountability in corporate governance is to ensure that companies operate openly, honestly and in accordance with the rules. The law regulates information disclosure, internal supervision, and protection of shareholders rights, while providing sanctions for violations, in order to create responsible governance and high integrity.